2021
DOI: 10.1016/j.jvs.2020.04.499
|View full text |Cite
|
Sign up to set email alerts
|

Cause-specific mortality of type B aortic dissection and assessment of competing risks of mortality

Abstract: Objective: Natural history studies of type B aortic dissection (TBAD) commonly report all-cause mortality. Our aim was to determine cause-specific mortality in TBAD and to evaluate the clinical characteristics associated with aorta-related and nonaorta-related mortality.Methods: Clinical and administrative records were reviewed for patients with acute TBAD between 1995 and 2017. Demographics, comorbidities, presentation, and initial imaging findings were abstracted. Cause of death was ascertained through a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 34 publications
1
5
1
Order By: Relevance
“…In Li et al’s study ( 21 ), the cut-off value of high-sensitivity cardiac troponin T for in-hospital death in aTAAD patients was 0.042, which was higher than 0.014. In our study, the major cause of death in TBAD patients the first year after TEVAR was aortic-related mortality (69.7%), which was consistent with that of Hysa et al’s study ( 22 ). In this context, the cut-off value of cTnI 0.029 may predict 1-year aortic-related mortality after TEVAR.…”
Section: Discussionsupporting
confidence: 92%
“…In Li et al’s study ( 21 ), the cut-off value of high-sensitivity cardiac troponin T for in-hospital death in aTAAD patients was 0.042, which was higher than 0.014. In our study, the major cause of death in TBAD patients the first year after TEVAR was aortic-related mortality (69.7%), which was consistent with that of Hysa et al’s study ( 22 ). In this context, the cut-off value of cTnI 0.029 may predict 1-year aortic-related mortality after TEVAR.…”
Section: Discussionsupporting
confidence: 92%
“…Mortality rates following uTBAD have previously been reported to approach 30% at 3 to 5 years, but we found 5-year mortality of 44.5%, which may, in part, reflect the older age of the cohort as well as complete outcome ascertainment. We also found hospitalization rates that were higher than previously reported primarily in single-institution or institution-linked registries, highlighting the limitations of institution-centered analyses .…”
Section: Discussioncontrasting
confidence: 67%
“…Sex differences in AAD have received attention due to higher in-hospital or short-term mortality in women with TAD, while both type A and B AADs show approximately twice as frequently in men [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Several studies revealed a later age of AAD onset in females compared with males, and more pharmacotherapy and aortic rupture prior to intervention in women are likely the cause of the early outcome difference [ 15 , 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%